Pre-Analytical Errors in Clinical Diagnostic Laboratory: A Crucial Step to Look for Accuracy and Reliability (Indian Journal of Forensic Medicine & Toxicology, 2020)
Clinical Diagnostic Laboratory (CDL) plays a very important role in diagnosis and treatment of diseases.Total testing process (TTP) of laboratory includes pre-analytical, analytical and post-analytical phases. Tohave an accurate and reliable results, detection and prevention of errors is must from all these phases.Chances of errors are more in pre-analytical phase as compared other two phases. Though standards havebeen made to control error occurrence in pre-analytical phase, errors still noticed in this phase. The reasonis all the steps involved in this phase are dependent on humans and thus it is out of control of laboratory.Therefore it is necessary to generate proper guidelines or manual to minimize errors in pre-analytical phase.This is also an important step to achieve Total Quality Control (TQC). We have tried in this review tosummarize important pre-analytical errors, their occurrence at various stages, prevalence and preventiveaspects.